2018
DOI: 10.1016/j.pec.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Informing physician strategies to overcome language barriers in encounters with pediatric patients

Abstract: By identification of specific positive and negative behavioral adaptations, this study emphasizes intervention targets, such as demonstrating interest in an LEP pediatric patient's family story and individuality and using common niceties in conversations with LEP children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…20 Whereas, distrust in physicians is a stumbling block to communication as the patient may not share important information or ask important questions. 17 Another highly documented theme that appeared in the literature and is consistent with the results of our study was the lack of satisfaction with the healthcare system including their physician due to language barriers. 7 It was cited in an article by Um and Lau that dissatisfaction among patients is associated with higher mortality rates and poor treatment outcomes.…”
Section: Misinterpretation Of Treatmentsupporting
confidence: 88%
“…20 Whereas, distrust in physicians is a stumbling block to communication as the patient may not share important information or ask important questions. 17 Another highly documented theme that appeared in the literature and is consistent with the results of our study was the lack of satisfaction with the healthcare system including their physician due to language barriers. 7 It was cited in an article by Um and Lau that dissatisfaction among patients is associated with higher mortality rates and poor treatment outcomes.…”
Section: Misinterpretation Of Treatmentsupporting
confidence: 88%
“…One reason for this may be the one Llopis [28] points out, namely that the use of ad hoc interpreters can come from the fact that healthcare personnel do not understand the risk involved in communicating through ad hoc interpreters. Another reason could be a lack of time, because time has been identified as one of the most important barriers in interactions with families that do not speak the majority language [29]. In a study by Jaeger et al [30], however, the respondents viewed the use of professional interpreters as time consuming, but the alternative of not using a professional interpreter was viewed as even more time consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, interpreter-mediated communication adds complexity that warrants further investigation. Existing literature regarding interpreted healthcare encounters suggests that patient-provider communication benefits from a combination of traditional and nontraditional practices to forge an effective working alliance between clinicians and interpreters (Brisset, Leanza, & Laforest, 2013;Guerrero, Small, Schwei, & Jacobs, 2018;Mirza, Harrison, Chang, Salo, & Birman, 2017). For example, Mirza et al (2017) found that effective communication with refugee patients in the mental healthcare setting was less about interpreters' performance and more about performance of a three-way communication system.…”
Section: Introductionmentioning
confidence: 99%